Psychological factors and physical outcomes in patients with chronic diseases of lifestyle - Skowno, Philippa (MRC/UCT RU for Exercise and Sport Medicine, 2016)
INTRODUCTION: Chronic diseases of lifestyle (CDL) are a major cause of global morbidity and mortality. Although CDL are largely preventable and treatable through adopting and maintaining healthy lifestyle behaviours, CDL rehabilitation programmes remain an underutilised resource. Behaviour modification is thus complex, and requires a collaborative approach between psychologists and medical clinicians involved in the management of CDL. This thesis examined the role of psychological factors in the management of patients with CDL who participated in a comprehensive lifestyle intervention (CLI) programme. METHODS: An explanatory mixed methods design was used to describe the CLI experience. These included an initial clinical audit of 308 patients commencing and completing a twelve week CLI programme to test associations of psychological, demographic, medical and diagnostic factors with physical outcomes. Two qualitative studies were subsequently conducted to further understand patient experiences of CDL and CLI programmes. The first involved interviews of 14 patients at programme commencement and completion. The second consisted of a case study of a patient participating in the programme using human centred design principles as well as ethnography.